Nasopharyngeal cancer diagnosis with optical coherence tomography - Ng, Beng Koon. (2008)
Two optical coherence tomography (OCT) systems were implemented in this work to extend the scope of an on-going research project, funded by the Singapore Cancer Syndicate to investigate the use of OCT for early nasopharyngeal cancer (NPC) diagnosis. The first OCT system is designed around a 1300 nm broadband superluminescence diode (SLD) source using the time-domain method. An axial resolution of 10 μm and an imaging depth of more than 2.5 mm were obtained with this system. An existing time-domain 800 nm OCT system based on a Ti:Sapphire laser source is modified into a Fourier-domain system using a nearinfrared (NIR) spectrometer. This eliminates the need for mechanical scanning on the reference arm of the OCT system and improves the imaging time by a factor of 3.7.